The expression of apoptosis inducing factor (AIF) is associated with aging-related cell death in the cortex but not in the hippocampus in the TgCRND8 mouse model of Alzheimer’s disease - Yu, Wenfeng (BioMed Central, 2014)
BACKGROUND: Recent evidence has suggested that Alzheimer’s disease (AD)-associated neuronal loss may occur via the caspase-independent route of programmed cell death (PCD) in addition to caspase-dependent mechanisms. However, the brain region specificity of caspase-independent PCD in AD-associated neurodegeneration is unknown. We therefore used the transgenic CRND8 (TgCRND8) AD mouse model to explore whether the apoptosis inducing factor (AIF), a key mediator of caspase-independent PCD, contributes to cell loss in selected brain regions in the course of aging. RESULTS: Increased expression of truncated AIF (tAIF), which is directly responsible for cell death induction, was observed at both 4- and 6-months of age in the cortex. Concomitant with the up-regulation of tAIF was an increase in the nuclear translocation of this protein. Heightened tAIF expression or translocation was not observed in the hippocampus or cerebellum, which were used as AD-vulnerable and relatively AD-spared regions, respectively. The cortical alterations in tAIF levels were accompanied by increased Bax expression and mitochondrial translocation. This effect was preceded by a significant reduction in ATP content and an increase in reactive oxygen species (ROS) production, detectable at 2 months of age despite negligible amounts of amyloid-beta peptides (Aβ). CONCLUSIONS: Taken together, these data suggest that AIF is likely to play a region-specific role in AD-related caspase-independent PCD, which is consistent with aging-associated mitochondrial impairment and oxidative stress.